PROSPECTS FOR THE DEVELOPMENT OF INNOVATIVE AGRICULTURE IN UZBEKISTAN (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Uzbekistan, a country with a rich agricultural heritage, faces numerous challenges in its agricultural sector, including climate change, soil degradation, and inefficient farming practices. To overcome these challenges, the adoption of innovative agricultural techniques is essential. This article explores the prospects for developing innovative agriculture in Uzbekistan, emphasizing the benefits of technology integration, government support, and sustainability practices. It presents an overview of the current trends, potential investment opportunities, and obstacles to innovation in the agricultural sector, highlighting the importance of modernizing agriculture to enhance productivity, economic sustainability, and food security.